CORRELATION BETWEEN MALOCCLUSION OF THE ANTERIOR AND PSYCHOSOCIAL CONDITION OF TEENAGERS IN BANJARMASIN - Irnamanda DH; Talitha Fatimah Rahma; Tri Nurrahman; Melisa Budipramana; Galuh Dwinta Sari (FKG ULM, 2025)
Background: Malocclusion creates problems in mastication, swallowing, speech, high risk of trauma, periodontal disease, caries and decreased aesthetic which can affect psychosocial. People with malocclusion often receive poor response from others, such as insults or inappropriate nicknames. The psychological effects on people with malocclusion include inferiority, embarrassment, difficulty in adaptation, emotional disorder, lack of confidence, uncomfortable social interaction, unhappy, and often compare themselves with others will affect a person’s development, especially during adolescence. Purpose: The purpose of this research was to know about correlation between the malocclusion of the anterior with the psychosocial in adolescent at Banjarmasin.. Methods: This research is an observational analytic using cross sectional approach. The sample size using Lemeshow in this research was 356 students. Data collection was performed using IOTN-AC and PIDAQ questionnaire. Data analysis consists of univariate analysis which describing each variable and bivariate analysis which connected two variables with Spearman test. Results: The orthodontic treatment needs at Banjarmasin based on the highest IOTN-AC was in the category no of need the treatment were about 158 people (44%). The psychological condition in adolescent based on the highest PIDAQ was on the student with the category of currently were about 163 people (45,7%). Conclusion: The Spearman result showed that the significance value is less than 0.05. Concluded that there was a significant correlation between orthodontics treatment needs with the psychosocial condition of adolescent.